polski: Structural evolution in the cooperative banking sector in the years 1996-2011 - Kozak, Sylwester (Management and Administration Journal, 2021)
In the period 1996-2011 the co-operative banking sector was the subject of a strong structural transformation, evolving from niche banking to universal banking. These processes were similar to changes taking place in the EU and beyond. The number of banks has decreased more than half (from 1394 to 574), but the size of the branch network increased (from 1136 to 4020). Consolidation has helped to improve the capitalization of banks, and the level of security of their actions. The average value of the capital adequacy ratio increased from 8.8% to 13.4%. Higher equity loans allowed them to service larger companies. Polish accession to the EU, the economic recovery and the global financial crisis resulted in the reorganization of the structure of cooperative banks’ loan portfolio significantly increasing the share of loans to companies and individuals, and reducing the share of loans to farmers.